Polarisation in the auroral red line during coordinated EISCAT Svalbard Radar/optical experiments - M. Barthélémy; J. Lilensten; F. Pitout; C. Simon Wedlund; R. Thissen; D. Lorentzen; F. Sigernes; J. Moen; G. Gronoff; I. McCrea; H. Rothkael; H. Ménager; et al. (Annales Geophysicae, 2011)
The polarisation of the atomic oxygen red line in the Earth's thermosphere is observed in different configurations with respect to the magnetic field line at high latitude during several coordinated Incoherent Scatter radar/optical experiment campaigns. When pointing northward with a line-of-sight nearly perpendicular to the magnetic field, we show that, as expected, the polarisation is due to precipitated electrons with characteristic energies of a few hundreds of electron Volts. When pointing toward the zenith or southward with a line-of-sight more parallel to the magnetic field, we show that the polarisation practically disappears. This confirms experimentally the predictions deduced from the recent discovery of the red line polarisation. We show that the polarisation direction is parallel to the magnetic field line during geomagnetic activity intensification and that these results are in agreement with theoretical work.